Voltage unbalance assessment in a distribution system incorporated with renewable‐based sources and electric vehicles in an uncertain environment - Nandini K. K.; Jayalakshmi N. Sabhahit; Vinay Kumar Jadoun (IET Renewable Power Generation)
Abstract This work aims to assess the impact of electric vehicles (EVs) and renewable energy sources (RESs) on the voltage unbalance factor (VUF) and a combined assessment of distribution network operational parameters such as voltage stability, reliability and power loss (VRP) index on modified IEEE 33 bus system under three distinct operational cases. A severe power quality issue such as voltage unbalance can result from integrating RESs and EVs with the distribution system. It effects the performance and durability of the consumer side as well as power system equipment. A coordinated charging–discharging strategy of EVs with RESs is proposed to keep the VUF within the acceptable limit. Solar and wind energies are uncertain and often unavailable at the time of load demand, which is modelled by Monte‐Carlo Simulation (MCS) for effective energy management. The fuel cell is used as a backup source to handle the variability of solar and wind energies. The proposed problem is solved using two different optimization methods i.e., a modified version of JAYA and whale optimization algorithm (WOA) using MATLAB software. The modified WOA outperforms the other optimization method and the existing literature in minimizing the % VUF and VRP index in case 2 operation, with values of 1.7 and 8.89 respectively. Case 3 also achieves low objective function values, but the VUF and VRP index are 11.76% and 9.67% higher than case 2 by modified WOA. This demonstrates the efficacy of the proposed approach and the proper uncertainty modelling of sources.